Networks, Genres, and Complex Wholes: Citizen Science and How We Act Together through Typified Text - Kelly, Ashley Rose; Maddalena, Kate (Canadian journal of communication, 2016)
This article explores the intersection of Rhetorical Genre Studies (RGS) and Actor-Network Theory (ANT). These two traditions are particularly important in the Canadian research context. We examine genre and ANT to uncover what we believe is a complementary relationship that promises much to the study of science, especially in the age of the internet. Specifically, we see RGS as a way to account for how objects come to “be” as complex wholes and so act across/among levels of network configurations. Moreover, the nature of these objects’ (instruments’) action is such that we may attribute them to a kind of rhetorical agency. We look to the InFORM Network’s grassroots, citizen science-oriented response to the Fukushima Daiichi nuclear disaster as a case that exemplifies how a combined RGS and ANT perspective can articulate the complex wholes of material/rhetorical networks.